A Santa Casa de Misericórdia de Cuiabá (1817-1930) : assistencialismo, práticas médicas, memórias e razões de Estado - Santos, Marcia Adriana dos (2015)
In Portugal, was founded in August 15, 1498, the first Mercy, originating from a process called hospitals reforms. This Mercy, in Lisbon, is due in large part to the figure of Queen Leonor, who spread the idea of mercy as aid to the needy, due to a higher goal that was forming a spirituality. The first Brazilian Mercy were founded in the colonial period. The service practiced by Mercy in Brazil, under royal authorization was given by the ruling elite, with strategies to ensure their privileges a secular character of the institution, but under the influence of the Catholic Church. The Mercy in Mato Grosso land was possible due to the legacy of Manuel Fernandes Guimarães, the Captain-General João Augusto D'Oyennhausen and Gravenburg, was responsible for the administration of the amount donated. Completed the construction of the hospital of Lazarus in 1816, with the help of donations, started building the hospital of Our Lady of the Conception of Mercy in Cuiaba, opened in 1817. The fear of epidemics such as smallpox which reached Cuiaba in 1867, did with the State began to apply preventive measures related to health and public hygiene. Social protection policies have emerged as the state's infrastructure progressed. Donations were made by the population in order to minimize the difficulties and spread the spirit of solidarity, values left in wills, real estate, jewelry, slaves, and donated valuables, some in life. In the early twentieth century the state of Mato Grosso following a national health policy plan implemented projects that would make a public health issue.